Strategi Pembelajaran Daring Dalam Meningkatkan Prestasi Siswa Pada Mata Pelajaran Fikih di MI Al-Hasyimiyah Jakarta Barat - Naila Auliya Rahmah; Hasanah (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
This research aims to find out online learning strategies in improving student achievement in jurispruded subjects and to find out the factors that are inhibiting and supporting it and to find out the success of online learning strategies in improving student achievement in jurispruded subjects in MI al-Hasyimiyah West Jakarta. The type of research used in this research is qualitative with a qualitative descriptive type of research. The primary data source used was obtained from field observation techniques and interviews to 1 teacher of jurispruding subjects, the principal, and 3 students of MI al-Hasyimiyah West Jakarta. Secondary data sources are obtained from books, journals, and other scientific writings that support research. And the source of documentary data obtained in the form of school profiles, learning activities, and photos. The results showed that the strategies used by a jurist teacher run effectively and efficiently, the strategies used lead more to the strategy of learning inquiry. Inhibiting factors include limited quota packages, internet signal interference, different economic factors, and the ability of teachers and students to master internet learning applications. While supporting factors include the existence of infrastructure facilities provided by madrasahs (WIFI, computers, and others), the good health of teachers and students, as well as the support and motivation of parents for their children during online learning. KKM at MI Al-Hasymiyah is 80, and during the online learning process the students experience an increase in achievement for two semesters, the average value of MI Al-Hasyimiyah students can exceed the specified KKM. 70% of grade VI B students experienced an increase in report card scores and teachers were satisfied with their success in teaching during the Covid-19 pandemic.